Country image and media (2004–2023): a bibliometric analysis - Jin, Fangfang; Abdul Latiff Ahmad; Shamsiah Abd Kadir (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this globalization and information era, global uncertainties and challenges are increasing. Moreover, there is a larger stage for countries to improve themselves. Media play a crucial role in shaping country image, especially communicating a better country image. This study provides an overview of the research trends, key contributors, and hotspots on country image and media from 2004 to 2023 through bibliometric analysis using VOSviewer, R-bibliometrix, and Excel. Findings indicate that China and the United States lead the research, with key topics including diplomacy, mass media, and mega-events like the Olympics. According to the purpose of study, 260 articles from 57 countries and 545 authors were analysed. The articles of China and the United States took up more than half of all. Hong Kong polytechnic university, Tsinghua university and Nanyang technological university are main research institutions. The journal of Place branding and public diplomacy made the largest influence in the field. For all of 545 authors, Kim Seongseop appeared three rankings of publications, citations and co-citations. “Country image”, “mass media”, “diplomacy”, “Olympic Games”, “China”, “Covid-19” and others are main keywords and topics. These findings provide a reference for scholars to research country image and media, and encourage other scholars explore more research perspectives about the research field.